Tailoring the mechanical and degradation properties of 3DP PLA/PCL scaffolds for biomedical applications - Sumama Nuthana Kalva (17302906) (2025)
In the realms of tissue engineering and 3D printing, tailoring scaffold mechanical characteristics and degradation rates is crucial for superior performance in a range of biomedical settings. This research explores the use of poly(lactic acid) (PLA) and poly(ε-caprolactone) (PCL) blends as feedstocks for fused deposition modeling. We fabricated filaments using five different PLA/PCL ratios (100/0, 70/30, 50/50, 30/70, and 0/100) and utilized them to fabricate test samples using a 3D printer. This study assesses how PCL influences the thermal, physicochemical, and printing properties of PLA. The introduction of PCL, which has a lower melting point and greater ductility compared to PLA, not only enhances printability but also adds flexibility and governs the degradation pace of the scaffolds. Fourier transform infrared spectroscopy analysis reveals that the chemical functional groups of PLA and PCL are quite similar, leading to significantly overlapping infrared bands in the blends. PLA (70%) exhibits a high elastic modulus (1.23 GPa) and maximum tensile strength (32.5 MPa), demonstrating that it maintains its rigidity and strength despite the substantial inclusion of PCL. Furthermore, an increase in PCL content correlates with a reduction in weight loss, indicating slower degradation rates in phosphate-buffered saline. Our results provide a deeper understanding of how PLA/PCL ratios affect scaffold properties, offering important insights for creating custom scaffolds that meet specific needs in tissue engineering applications. Other Information Published in: REVIEWS ON ADVANCED MATERIALS SCIENCE License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1515/rams-2025-0098